Răspunsuri

2014-05-08T15:50:25+03:00
A)5,7 x +7,2=3,5 x +38 ⇔5,7x-3,5x=38-7,2
                                       2,2X=30,8
                                      X=14
b)2,4x+0,3x=14,4 +1,5x⇔2,4x + 0,3x - 1,5 x= 14,4
                                       1,2x = 14,4
                                           x=12
c)7,9x +  11,6=14,3x - 5,9x⇔7,9x + 5,9c - 14,3x = -11,6
                                                    -0,5x = -11,6
                                                         x=23,2
d)3x +14,32=2x +56,98⇔3x-2x = 56,98 - 14,32
                                              x=42,66
e)4,8x + 54,9= 17,2x - 11,4x⇔ 4,8x -17,2x + 11,4x = 54,9
                                                   -x = 54,9
                                                    x = -54,9